2019
DOI: 10.35808/ijeba/266
|View full text |Cite
|
Sign up to set email alerts
|

Customs’ Control on Genetically Modified Food Products Across the Border of the Eurasian Economic Union

Abstract: Purpose: The purpose of the article is to determine the role of customs' control and directions of its improvement in the movement of genetically modified foods across the customs' border of the Eurasian Economic Union. In carrying out the study, the authors rely on the methods of theoretical modeling and interpretation of legal concepts and normative legal acts, which allowed to identify theoretical and applied problems of customs control in the conditions of Eurasian integration. Design/Methodology/Approach:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…From the result, it can be inferred that limited regulatory monitoring processes such as that of the GMO testing laboratory require policy intervention in strengthening and reducing regulatory administrative burdens. However, Grechkina et al (2019) concluded that the implementation of customs control over cross border movement of GMO foods improves efficiency and ensures the protection of the rights of citizens of the EAEU member States. Therefore, Namibia have developed and gazetted a genetically modified product list even though there is still a need to implement border control to sample GMO product consignments entering Namibia to ensure that permits granted are adhered to.…”
Section: Impact Of Labelling Regulationsmentioning
confidence: 99%
“…From the result, it can be inferred that limited regulatory monitoring processes such as that of the GMO testing laboratory require policy intervention in strengthening and reducing regulatory administrative burdens. However, Grechkina et al (2019) concluded that the implementation of customs control over cross border movement of GMO foods improves efficiency and ensures the protection of the rights of citizens of the EAEU member States. Therefore, Namibia have developed and gazetted a genetically modified product list even though there is still a need to implement border control to sample GMO product consignments entering Namibia to ensure that permits granted are adhered to.…”
Section: Impact Of Labelling Regulationsmentioning
confidence: 99%